Philosophical Concept of Space and Time: Michel Foucault dan Gilles Deleuze - Stephanus Djunatan (Extension Course Filsafat ( ECF ), 2019)
Philosophical Concept of Space and Time: Michel Foucault dan Gilles Deleuze